Kenya's Search for Truth and Justice: The Role of Civil Society. (12th April 2014) - Bosire, Lydiah Kemunto; Lynch, Gabrielle
Abstract 1 : This article describes the role of Kenyan civil society in two attempts to achieve 'truth' and 'justice' through a Truth, Justice and Reconciliation Commission (TJRC). The first occurred in 2003, when a change of political leadership led to the creation of a Task Force on the Establishment of a TJRC (TF), and the second occurred from 2008 to 2013, when a postelection crisis led to the formation of a coalition government and the institution of a widely criticized TJRC. In both instances, the fate of the exercise depended in large part on civil society organizations: the alliances they made, the arguments they mobilized, the support and criticisms they provided and their interactions with citizens, media, international donors, state actors and TF or Commission staff. Civil society approaches were also shaped by a combination of their individual and collective understandings of what constituted the most important issues and best practice, and their interpretations of government motivations, and thus by what was deemed possible, and to be feared, in working with such a state-led initiative. The article suggests that truth commissions are not a discrete tool that can be applied with the same effect in any setting, and that transitional justice actors must pay greater attention to local politics and dynamics in establishing truth commissions, including the capacity, concerns and interests of local civil society organizations, which have the power to either bolster or undermine such a project.